2016
DOI: 10.1109/tdei.2015.005378
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on relationship between breakdown strength enhancement of composites and dielectric characteristics of nanoparticle

Abstract: In this work, the relationship between dielectric characteristics of nanoparticle and its effects on dielectric breakdown strength of Epoxy was investigated. The dielectric characteristic was tailored through silica surface encapsulation on TiO2. It was found that in contrast to raw TiO2, addition of TiO2@SiO2 core-shell nanoparticle obviously improved the dielectric breakdown strength of epoxy resin. Meanwhile, peculiar increase of resistivity was also observed. Based on the results, a mechanism through "barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…As reported by many researchers previously, this study also indicated that every NP has an optimum concentration threshold at which it gives maximum benefit. This percentage is usually below 1 percent by weight in the for many kinds of base material [20][21][22]26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by many researchers previously, this study also indicated that every NP has an optimum concentration threshold at which it gives maximum benefit. This percentage is usually below 1 percent by weight in the for many kinds of base material [20][21][22]26].…”
Section: Resultsmentioning
confidence: 99%
“…5 wt% of nano-ATH showed equivalent results to 20 wt% of micro SiO 2 . Chen and Wu [20] used TiO 2 @SiO 2 core-shell nanoparticles in epoxy and concluded an increase in resistivity and dielectric breakdown strength when the nano-fillers were less than 1% by weight. The reason to this enhancement is the barrier effect, which is basically the formation of electrical double layer between inorganic (TiO 2 @SiO 2 ) and organic (epoxy).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [17] investigated the dielectric properties of TiO 2 and TiO 2 @SiO 2 epoxy nano composites. It was observed that TiO 2 @SiO 2 nano composite gives higher breakdown strength and lower LC than TiO 2 nano composites.…”
Section: Efforts Done In Previous Studiesmentioning
confidence: 99%
“…As suggest by the BET specic area measuring results (Table 1), there is tremendous interface between the two discontinuous dielectrics where mobile charges accumulate according to the Maxwell-Wagner theory and polarize under the alternating external eld. 31 Consequently, the resulted interfacial polarization will contribute to the improvement of the EM wave dissipation efficiency as widely acknowledged. 32 Furthermore, regarding to the specially designed structure of Ni/DMC in present work, it is also anticipated to make a difference on the EM wave multi-reection.…”
Section: Microwave Absorption Propertiesmentioning
confidence: 99%